Rekonstruksi Pertanggungjawaban Pidana Korporasi dalam Undang-undang Nomor 1 Tahun 2023 Tentang KUHP - Hermawan, Hermawan; Waluyo , Agus Jati (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
Indonesian criminal law, as reflected in the Criminal Code (WvS), adheres to the principle of universitas delinquere non potest or societas delinquere non potest. This principle asserts that legal entities (corporations) cannot commit crimes; only natural persons (natuurlijke persoon) can be held criminally liable. With economic development and industrialization, corporations are no longer viewed as passive business entities, but rather as key actors with the potential to cause massive losses to the state, society, and the environment. This situation forces criminal law to evolve by recognizing corporations as legal subjects. The enactment of Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code) marks a significant milestone in Indonesian criminal law reform. One fundamental change is the explicit inclusion of corporations as subjects of criminal law in general provisions. This regulation is crucial for creating legal certainty and justice. With this recognition, law enforcement officials now have a stronger and more uniform legal basis for prosecuting corporations that commit crimes.